2012
DOI: 10.1007/s11745-012-3669-y
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Arachidonate Restores the Dimethoate‐Induced Inhibition of Steroidogenesis in Rat Interstitial Cells

Abstract: The present work studies the potential restorative effect of polyunsaturated fatty acids (PUFA, 5 μM/24 h) on the dimethoate (DMT)‐induced inhibition of testosterone biosynthesis in Leydig cells isolated from rat testes. Various fatty acids (FA) from the n‐6 (18:2, 20:3, 20:4, 22:4 and 22:5) and n‐3 (18.3, 20:5, 22:5, 22:6) series were assayed in Leydig cells, alone (as delipidated BSA complexes) and in combination with DMT (1 ppm). The n‐6 FA stimulated lipid peroxidation (LPO) and inhibited the activities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…This finding supports previous human macrophage studies which indicated that SFA induced cox2 expression (Lee et al, 2001;Rocha et al, 2016). Astiz et al (2012) showed that addition of 22:4ω6 and 22:5ω6 did not impact the production of COX2 in rat testis cells. However, a previous study on mouse brain indicated that reduction in the levels of ARA metabolites 22:4ω6 and 22:5ω6 reflected a shift of ARA from LC-PUFA biosynthesis prostaglandin or leukotriene synthesis (McNamara et al, 2009).…”
Section: Transcripts Involved In Eicosanoid Metabolismsupporting
confidence: 92%
“…This finding supports previous human macrophage studies which indicated that SFA induced cox2 expression (Lee et al, 2001;Rocha et al, 2016). Astiz et al (2012) showed that addition of 22:4ω6 and 22:5ω6 did not impact the production of COX2 in rat testis cells. However, a previous study on mouse brain indicated that reduction in the levels of ARA metabolites 22:4ω6 and 22:5ω6 reflected a shift of ARA from LC-PUFA biosynthesis prostaglandin or leukotriene synthesis (McNamara et al, 2009).…”
Section: Transcripts Involved In Eicosanoid Metabolismsupporting
confidence: 92%
“…In a previous work from our laboratory, we demonstrated that D displays a complex mechanism of action involving disturbance of testosterone production reducing both, the plasma and interstitial Leydig cell concentrations, damage to the antioxidant defense system, decrease araquidonate content in phospholipids, inhibit StAR protein expression with simultaneous stimulation of COX-2 (overproduction of PGF2a) and inhibition of the steroidogenic enzymes 17bHSD and 3bHSD (Astiz et al, 2009a). Damage caused to the steroidogenic status of Leydig cells exposed to D could be reverted by exogenous arachidonate (Astiz et al, 2012). Moreover, recent studies in rats suggested that exposure to G during the pre-and post-natal periods induced adverse effects on male reproductive performance (Dallegrave et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Dimethoate, a widely used organophosphate, was reported to reduce Leydig cell steroidogenic function in association with decreased arachidonate and increased COX-2 (Astiz et al . 2009, Astiz et al . 2012).…”
Section: Effects Of Environmental Factors On Steroidogenesismentioning
confidence: 99%